ANMCO position paper on antithrombotic treatment of patients with atrial fibrillation undergoing intracoronary stenting and/or acute coronary syndromes. (18th May 2022) - De Luca, Leonardo; Rubboli, Andrea; Lettino, Maddalena; Tubaro, Marco; Leonardi, Sergio; Casella, Gianni; Valente, Serafina; Rossini, Roberta; Sciahbasi, Alessandro; Natale, Enrico; Trambaiolo, Paolo; Navazio, Alessandro; et al.
Abstract: Patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) with or without acute coronary syndromes (ACS) represent a subgroup with a challenging pharmacological management. Indeed, if on the one hand, antithrombotic therapy should reduce the risk related to recurrent ischaemic events and/or stent thrombosis; on the other hand, care must be taken to avoid major bleeding events. In recent years, several trials, which overall included more than 12 000 patients, have been conducted demonstrating the safety of different therapeutic combinations of oral antiplatelet and anticoagulant agents. In the present ANMCO position paper, we propose a decision-making algorithm on antithrombotic strategies based on scientific evidence and expert consensus to be adopted in the periprocedural phase, at the time of hospital discharge, and in the long-term follow-up of patients with AF undergoing PCI with/without ACS.